Drowning of a patient with epilepsy while showering - Risako Nakagawa; Wataru Ishii; Masahito Hitosugi (Komiyama Printing Co. Ltd, 2019)
Abstract In Japan, because the most common site of drowning among patients with epilepsy is the bathtub, showering is generally recommended as an alternative to bathing. We herein report a case involving a female patient with epilepsy who drowned while showering. She had been diagnosed with epilepsy approximately 25 years previously, and her condition had progressed to refractory epilepsy. Carbamazepine, levetiracetam, lamotrigine, clobazam, and perampanel were prescribed daily. One day while showering, the patient was found lying with her face immersed in water that had accumulated on the floor of the bathtub. A forensic autopsy revealed water in the stomach, trachea, and proximal regions of both lung bronchi as well as white and red foam on the pharynx and larynx. A total of 1.9 μg/mL of lamotrigine, 0.14 μg/mL of carbamazepine, and 0.069 μg/mL of perampanel were detected in the patient's blood. The patient's cause of death was determined to be drowning due to an epileptic seizure. Although the patient was prescribed five types of antiepileptic medication, only three were detected in her blood. The current case demonstrates that drowning can occur while showering, suggesting that it is unsafe for patients with medication nonadherence. To prevent unintentional deaths in the bathroom, we recommend that patients with epilepsy maintain high adherence to all prescriptions and are supervised by a family member, even when showering. The current case is the first autopsy report of a patient with epilepsy who drowned while showering.